(untitled) (Research, Society and Development, 2021)
This study aimed to assess the sociodemographic profile, eating habits and knowledge of nutrition of vegetarian customers in a university restaurant. This is a cross-sectional study carried out with 3348 customers of a collective feeding establishment linked to a higher education institution in Vitória-ES, of which 196 were vegetarians. A semi-structured questionnaire was used with questions about sociodemographic profile, eating habits and knowledge about nutrition. The data were analyzed in SPSS, adopting p <0.05. In total, the participants were predominantly students (94.6%, n = 3166), with a median age of 21 years. The prevalence of vegetarianism was higher among students from courses in areas other than health (6.8%) and females (7.2%), p <0.001. Among vegetarians (n=196), there was a predominance of ovolactovegetarian (63.8%; n = 125) and vegans represented 10.2% (n = 20). The ethical motive was the most mentioned among the adherents (50.5%) and the majority reported looking for information about the practice in non-scientific sources such as internet sites (74,4%, n=134) e blogs (25.6%, n=46). The score referring to knowledge in nutrition ranged from 6 to 14, with a mean of 11.7 ±.1.52 and median of 12.0 points, higher for females (11.94±1.33, p = 0.006). The knowledge about the profile of vegetarians is essential to satisfy the needs of this public.